2007
DOI: 10.1111/j.1469-8749.2007.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyskinetic cerebral palsy: a population‐based study of children born between 1991 and 1998

Abstract: The aim of this study was to describe the epidemiology, aetiology, and clinical findings in dyskinetic cerebral palsy (CP)in a population-based follow-up study of children born between 1991 and 1998. Age range at ascertainment was 4 to 8 years and prevalence was 0.27 per 1000 live-births. Fortyeight children were examined (27 males, 21 females; mean age 9y, range 5-13y). Thirty-nine had dystonic CP and nine a choreo-athetotic subtype. Primitive reflexes were present in 43 children and spasticity in 33. Gross M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
141
4
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 39 publications
9
141
4
4
Order By: Relevance
“…[13][14][15] Dystonia is more prevalent than the choreoathetotic subtype 19 and commonly manifests as dystonic hyper tonia of the upper extremities, neck, and face with concomitant * The Activa RC neurostimulator system was used in all cases. Lead location was calculated in reference to the midpoint of the anterior commissureposterior commissure (AC-PC) line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Dystonia is more prevalent than the choreoathetotic subtype 19 and commonly manifests as dystonic hyper tonia of the upper extremities, neck, and face with concomitant * The Activa RC neurostimulator system was used in all cases. Lead location was calculated in reference to the midpoint of the anterior commissureposterior commissure (AC-PC) line.…”
Section: Discussionmentioning
confidence: 99%
“…These areas are particularly vulnerable given the high metabolic demands of the peri-and neonatal developmental periods. 5,13,14 In a study to investigate the MRI correlates of CP, the European Cerebral Palsy Study found that basal ganglia and thalamus damage was associated with dystonic CP in 75.6% (34 of 45 cases) of the study cohort. 5 The posteroventrolateral globus pallidus internus (GPi) has become a well-established target for deep brain stimulation (DBS) in both primary and secondary dystonia.…”
mentioning
confidence: 99%
“…It is important to consider the interference of involuntary movements, which is a characteristic of the disease, on the variability of performance, due to the inability to exclude the unwanted components from the movement trajectory 1 . Therefore, motor behaviors that do not follow an execution pattern for the same task may result in interference in the variables of velocity an time of execution; these are compared with the MACS score, and they may reflect a poor relation.…”
Section: Discussionmentioning
confidence: 99%
“…The dyskinetic cerebral palsy (DCP) is characterized by the presence of involuntary, uncontrolled and recurring movements, which are occasionally stereotyped, representing one of the most incapacitating forms of the disease due to severe motor compromise 1 . The involuntary movement can lead to discomfort, interfere in voluntary movements, limit and even prevent upper limb (UULL) functions, which results in worse performance of activities of daily living (ADL), such as clothing, diet and personal hygiene, once the reach, the prehension and the manipulation are damaged 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There were associated recurrent chest infections, feeding problems due to pseudobulbar palsy and refractory seizures. The child also developed choreoathetoid movements with dystonia possibly due to deep nuclear variety of neuronal necrosis involving the Thalamoputaminalregion 4 . Thus he exhibited Mixed spastic dyskinetic features.…”
mentioning
confidence: 99%